Simple division of rectourethral fistula as an alternative to ligation during laparoscopic repair of anorectal malformation - Zahra Al Matar; Sabreen Maqbool; Habib Zakaria; Ali Alassiri (SpringerOpen, 2022)
Abstract Background Various techniques are described to manage the rectourethral fistula during laparoscopic repair of anorectal malformation (LAARP). The fistula can be ligated with sutures, clips, staplers, or simply divided flushed with the urethra. Objective The aim of our study is to share our experience of simply dividing the rectourethral fistula during LAARP without ligation. Patients and methods A retrospective chart review conducted between January 2005 and April 2020 including male children with rectourethral fistula. The fistula was managed by laparoscopic simple division without ligation along with temporary urinary diversion. Results Twenty-six patients were included. None of the patients had short- or long-term urinary complications due to the technique used. All patients had a regular follow-up for a minimum of 1 year. Conclusion Simple division of rectobulbar or rectoprostatic fistula is a safe, easier alternative to ligation of the fistula during laparoscopic repair of ARM.